الرقابة القضائية على اعمال السلطة الوطنية المستقلة للانتخابات في الجزائر - بن عمر, حمزة; دربالي, موسى; ديدي, مبروك (University of Eloued جامعة الوادي, 2022)
اف استحداث السمطة الكطنية المستقمة للانتخابات كمنحيا صلاحية تنظي العممية الانتخابية كالاش ا رؼ عمييا بعيد عف السمطة التنفيذية كالادارة ككؿ لممرة الاكلى منذ استقلاؿ الج ا زئر يعد قفزة نكعية في حماية حريات الاف ا رد كلعؿ اى حرية تتمثؿ في حرية الشخص في اختيار مف ينكب عنو في المناصب كالاماكف التمثيمية ، الا أننا نعرؼ أف الرقابة ىي مف الامكر البدييية التي أتت بيا دستكريات القرف الحديث مف خلاؿ الاستقلاؿ المرف لمسمطات كرقابتيا لبعضيا البعض لتحكؿ دكف تغكؿ احداىا عمى الاخرل عمى سبيؿ تطبيؽ قاعدة السمطة تحد السمطة ، كىك ما يكصمنا الى مدل رقابة القضاء لمسمطة الكطنية المستقمة للانتخابات .The establishment of the Independent National Authority for Elections and giving it the authority to organize and supervise the electoral science away from the executive and administration as a whole for the first time since the independence of Algeria is a qualitative leap in protecting the freedoms of individuals. We know that censorship is one of the axioms brought about by the constitutions of the modern century through the flexible independence of the authorities and their control of each other to prevent one from conquering one over the other in order to implement the rule of authority that limits authority, which leads us to the extent of the judiciary's control of power Independent national elections.
مدكرة ماستر
Keywords: الرقابة القضائية ، العممية الانتخابية ، السمطة المستقمة ،الاستقلالية.